Analisis penyaluran bantuan sosial program keluarga harapan (PKH) dan bantuan pangan non tunai (BPNT) dinas sosial pada masyarakat Kabupaten Batu Bara - Pratiwi, Dara Citra; Imsar, Imsar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine the implementation of social security programs, in particular the Non-Cash Food Assistance (BPNT) and Family Hope Program (PKH) programs for communities in Batu Bara Regency for eligible or ineligible people who are recipients of the distributed aid funds. The stages of the research used were surveys and direct interviews with the Social Service of Batu Bara Regency. In addition, conducting direct field observations by collecting data on the homes of people who received Non-Cash Food Assistance (BPNT) and assistance for the Family Hope Program (PKH). The results of the study stated that in accordance with the response from the description of the conditions at the research location that the distribution of assistance carried out by the Batu Bara local government, in this case the manager of the Batu Bara Regency Social Service was declared to have followed the procedure, but the problem was that there were still many people living in poverty. . Therefore, it is necessary to collect data on the actual suitability of the data. This study aims to examine the implementation of social security programs, in particular the Non-Cash Food Assistance (BPNT) and Family Hope Program (PKH) programs for communities in Batu Bara Regency for eligible or ineligible people who are recipients of the distributed aid funds. The stages of the research used were surveys and direct interviews with the Social Service of Batu Bara Regency. In addition, conducting direct field observations by collecting data on the homes of people who received Non-Cash Food Assistance (BPNT) and assistance for the Family Hope Program (PKH). The results of the study stated that in accordance with the response from the description of the conditions at the research location that the distribution of assistance carried out by the Batu Bara local government, in this case the manager of the Batu Bara Regency Social Service was declared to have followed the procedure, but the problem was that there were still many people living in poverty. . Therefore, it is necessary to collect data on the actual suitability of the data.